The impact of the German Child Benefit on child well-being - Christian Raschke (Institute for the Study of Labor (IZA), 2012)
The German Child Benefit (Kindergeld) is paid to legal guardians of children as a cash benefit. This study employs exogenous variations in the amount of child benefit received by households to investigate the extent to which these various changes have translated into an improvement in the circumstances of children related to their well-being. I use the German Socio-Economic Panel to estimate the impact of a given change in the child benefit on food expenditures of households, the probability of owning a home, the size of the home, as well as the probability of parents' smoking, alcohol consumption, and parents' social activities such as traveling, visiting movie theaters, going to pop concerts, attending classical music concerts or other cultural events. Households primarily increase per capita food expenditures in response to increases in child benefit, and they also improve housing conditions. I do not find a significant effect of child benefit on parents' smoking or drinking, but parents of older children use the child benefit to pay for their social and personal entertainment activities.
Keywords: I38; D12; H31; 330; child benefit; fungibility of income; child well-being; Familienleistungsausgleich; Kinder; Lebensstandard; Lebensqualität; Deutschland